2022
DOI: 10.46328/ijemst.2158
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Instructional Intervention Based on the Use of Video-Worked Examples to Promote Elementary Students’ Science Process Skills

Abstract: Several reforms in national and international curricula have been implemented to introduce inquiry-based activities to promote different science process skills. Science skills require high cognitive effort for students and, thus, they need supports to develop them in an inquiry process. Among these supports, video-worked examples demonstrate how to perform these skills and provide students with a scheme for an inquiry activity. Recently, video-examples has been explored in primary and secondary education with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Then, a very high percentage of teachers (80%) reported that it mobilizes the attention, interest of students, an advantage that is reported in several studies (Berk et al, 2009;Koumi, 2006Koumi, , 2014Koumi, , 2015Koumi, , 2019Papadimitriou, 2014;Papadimitriou et al, 2020;Papadimitriou & Sofos, 2021;Sofos & Yasiranis, 2022). A high priority of statements (about 73% of respondents) was also reported to be the possibility to choose to pause and restart at any point and at any time, which is also found in several studies (Cattaneo et al, 2022;Cattaneo et al, 2019;Kant et al, 2017;Koum, 2015;Papadimitriou et al, 2020;Papadimitriou, 2014;Papadimitriou & Sofos, 2021;Pattier, 2021a;Sofos & Yasiranis, 2022;Solé -Llussà et al, 2022). More than half of the teachers reported skill development as an advantage.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Then, a very high percentage of teachers (80%) reported that it mobilizes the attention, interest of students, an advantage that is reported in several studies (Berk et al, 2009;Koumi, 2006Koumi, , 2014Koumi, , 2015Koumi, , 2019Papadimitriou, 2014;Papadimitriou et al, 2020;Papadimitriou & Sofos, 2021;Sofos & Yasiranis, 2022). A high priority of statements (about 73% of respondents) was also reported to be the possibility to choose to pause and restart at any point and at any time, which is also found in several studies (Cattaneo et al, 2022;Cattaneo et al, 2019;Kant et al, 2017;Koum, 2015;Papadimitriou et al, 2020;Papadimitriou, 2014;Papadimitriou & Sofos, 2021;Pattier, 2021a;Sofos & Yasiranis, 2022;Solé -Llussà et al, 2022). More than half of the teachers reported skill development as an advantage.…”
Section: Discussionsupporting
confidence: 55%
“…5) Can highlight distant concepts (such as space) and lengthen it (such as the collision of two cars) or slow down time, such as the growth of a flower, etc. (Cattaneo et al, 2022;Cattaneo et al, 2019;Kant et al, 2017;Koum, 2015;Papadimitriou, 2014;Papadimitriou et al, 2020;Papadimitriou & Sofos, 2021;Pattier, 2021a;Sofos & Yasiranis, 2022;Solé-Llussà et al, 2022). 6) Gives a sense of immediacy and highlights the most important points of a topic in a short period of time (Harsasi, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations